Present Status of Marine Radioecology in Bali and Lombok Waters: Distribution Study of 137Cs and Natural Radionuclides in Lombok Strait - Deddy Irawan Permana Putra; Heny Suseno (Journal Omni-Akuatika, 2017)
Abstract Lombok strait is outflow of water masses from the Pacific Ocean to the Indian Ocean by Indonesian Throughflow (ITF). Radioecology studies in these waters were including monitoring of natural and artificial radionuclide. This study aims to obtain baseline data of artificial radionuclide 137Cs that entering from the Pacific Ocean through the Makassar Strait. The sampling location were covered territorial waters of Bali and Lombok. A large volume sample preparation for the 137Cs analysis were performed by co-precipitation process using K4Fe(CN)6 and CuCl2 at pH 8-9. Measurement of the concentration activity of natural radionuclides and 137Cs were using Gamma HPGe spectrometer with 20 – 25 % efficiency. The result of this study indicate the average concentration of 40K 226Ra 212Pb 214Bi 228Ac 214Pb and 137Cs in the sediments of Strait Bali waters respectively 165.16 Bq kg-1, 25.11 Bq kg-1, 8.36 Bq kg-1, 7.51 Bq kg-1, 7.05 Bq kg-1, 6.68 Bq kg-1 and the lowest of 0.15 Bq kg-1. In the waters of Lombok concentration activity of radionuclides 40K 226Ra 212Pb 214Bi 228Ac 214Pb and 137Cs in the sediments was 172.00 Bq kg-1, 25.88 Bq kg-1, 10.10 Bq kg-1, 6.50 Bq kg-1, 6.39 Bq kg-1, 5.70 Bq kg-1 and 0,162 Bq kg-1. The concentration activity of 137Cs in seawater of Bali and Lombok respectively was 0.113 Bq m-3 and 0.644 Bq m-3. Keyword : Natural Radionuclide, 137Cs, Lombok Strait